PENGARUH VARIASI DIAMETER VENTURI KARBURATOR DAN JENIS BUSI TERHADAP DAYA PADA SEPEDA MOTOR BAJAJ PULSAR 180 DTS-I TAHUN 2009 - Ramadhani, Aziz (Jurnal Nosel, 2013)
The research lead to conclusion that: (1) There is an effect of carburetor venturi diameter variation to power on motorcycle Bajaj Pulsar 180 DTS-I 2009. This is shown by the results of the test data analysis, that Fobservasi = 3520.48 greater than Ftabel = 3.83 (Fobservasi > Ftabel) at 1% significance level. (2) There is the influence of the type of spark plug in motorcycle Bajaj Pulsar 180 DTS-I 2009. This is shown by the results of the analysis of test data, that Fobservasi = 38452.50 greater than Ftabel = 4.31 (Fobservasi > Ftabel) at 1% significance level. (3) There is interaction the carburetor venturi diameter variation and types of spark plug to power the motorcycle Bajaj Pulsar 180 DTS-I 2009. This is shown by the results of the analysis of test data, that Fobservasi= 1193.78 greater than Ftabel = 2.66 (Fobservasi > Ftabel) at significance level 1%. Maximum power of 12.1 HP acquired in size diameter 32 mm venturi carburetor, varying kinds of spark plug Denso U20 EPR 9.